2006
DOI: 10.1124/mol.106.027250
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Tritium-Labeled Analog of L-threo-β-Benzyloxyaspartate Binding to Glutamate Transporters

Abstract: L-Glutamate is the major excitatory neurotransmitter in the mammalian central nervous system. Termination of glutamate receptor activation and maintenance of low extracellular glutamate concentrations are primarily achieved by glutamate transporters (excitatory amino acid transporters 1-5, EAATs1-5) located on both the nerve endings and the surrounding glial cells. To identify the physiological roles of each subtype, subtype-selective EAAT ligands are required. In this study, we developed a binding assay syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…These types of studies showed that aspartate binding is coupled to the binding of at least two sodium ions, whereas the binding of TBOA is coupled to the binding of one sodium ion. The latter is consistent with the observation that binding of a radiolabeled TBOA analogue to eukaryotic glutamate transporters requires only one sodium ion (12). Moreover, the authors observed that lithium and thallium (Tl ϩ ), but not potassium, can substitute for sodium in the binding assay, albeit with a very low apparent affinity.…”
supporting
confidence: 85%
“…These types of studies showed that aspartate binding is coupled to the binding of at least two sodium ions, whereas the binding of TBOA is coupled to the binding of one sodium ion. The latter is consistent with the observation that binding of a radiolabeled TBOA analogue to eukaryotic glutamate transporters requires only one sodium ion (12). Moreover, the authors observed that lithium and thallium (Tl ϩ ), but not potassium, can substitute for sodium in the binding assay, albeit with a very low apparent affinity.…”
supporting
confidence: 85%
“…It has previously been demonstrated that 4MG, threo-3-methylglutamate, TBOA, and kainate are competitive blockers of EAAT2 (12,14,15), so K i values were calculated from IC 50 values using the Cheng-Prusoff equation (16).…”
Section: Expression Of Transporters In Xenopus Laevis Oocytes and Elementioning
confidence: 99%
“…Only a few inhibitors of EAAT4 or EAAT5 have been characterized in electrophysiological studies because the glutamate uptake capacities of these subtypes are much lower than those of EAAT1–3 63. Therefore, to develop a novel binding assay system for the evaluation of all EAAT subtypes, we synthesized a tritium‐labeled TBOA analog, [ 3 H]ETB‐TBOA ( 56 ) (Scheme ) 64. [ 3 H]ETB‐TBOA showed specific, high‐affinity binding to rat brain crude membranes or EAAT‐transfected COS‐1 cell membranes expressing each EAAT subtype.…”
Section: Syntheses Of Functionalized Tboa Derivativesmentioning
confidence: 99%